2011
DOI: 10.1104/pp.110.167965
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interaction between CCaMK and a Protein Containing the Scythe_N Ubiquitin-Like Domain in Lotus japonicus        

Abstract: In the Rhizobium-legume symbiosis, calcium/calmodulin-dependent protein kinase (CCaMK) is a key regulator for both rhizobial infection and nodule organogenesis. Deregulation of CCaMK by either a point mutation in the autophosphorylation site or the deletion of the carboxyl-terminal regulatory domain results in spontaneous nodule formation without rhizobia. However, the underlying biochemical mechanisms are poorly understood. Here, using the kinase domain of CCaMK as a bait in yeast two-hybrid screening, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…The ROP6 RNAi hairy roots were inoculated with a lacZlabeled strain of M. loti, which provided a marker for identification of ITs after staining with 5-bromo-4-chloro-3-indolyl-b-D-galactopyranoside (X-gal) solution (Kang et al, 2011;Chen et al, 2012). Nine days after Rhizobium inoculation, the cellular locations and the numbers of ITs in the RNAi hairy roots were recorded.…”
Section: Decreases In Infection Thread Formation and Nodulation By Romentioning
confidence: 99%
“…The ROP6 RNAi hairy roots were inoculated with a lacZlabeled strain of M. loti, which provided a marker for identification of ITs after staining with 5-bromo-4-chloro-3-indolyl-b-D-galactopyranoside (X-gal) solution (Kang et al, 2011;Chen et al, 2012). Nine days after Rhizobium inoculation, the cellular locations and the numbers of ITs in the RNAi hairy roots were recorded.…”
Section: Decreases In Infection Thread Formation and Nodulation By Romentioning
confidence: 99%
“…Ca 2+ binding to the three EF hands in the VLD induces a change in the tertiary structure of CCaMK, activates its kinase activity, and also makes the Thr-271 accessible for autophosphorylation (state 2, transient and active, may phosphorylate substrates; Sathyanarayanan et al, 2000Sathyanarayanan et al, , 2001Gleason et al, 2006;Swainsbury et al, 2012). Thr-271 was reported to be the preferred and likely the first autophosphorylated site of CCaMK (Sathyanarayanan et al, 2001;Routray et al, 2013) Messinese et al, 2007;Yano et al, 2008;Kang et al, 2011). In addition, CaM binding could protect Ser-343 and Ser-344 from being phosphorylated by CCaMK, which is supported by the in vitro phosphorylation assays that demonstrated that CaM binding decreases the autophosphorylation level of CCaMK .…”
Section: Proposed Activation Mechanism Of Ccamkmentioning
confidence: 99%
“…An M. loti strain labeled with lacZ (Tansengco et al, 2003;Kumagai et al, 2006;Kang et al, 2011) was used to infect hairy roots. In SIP2 RNAi hairy roots, the initiation of ITs and IT growth could still be observed ( Figure 5E).…”
Section: Suppression Of Infection Thread Formation and Nodule Initiatmentioning
confidence: 99%